Systematic studies of the South African Campanulaceae sensu stricto with and emphasis on generic delimitations - Cupido, Christopher Nelson (Department of Biological Sciences, 2014)
The South African Campanulaceae sensu stricto, comprising 10 genera, represent the most diverse lineage of the family in the southern hemisphere. In this study two phylogenies are reconstructed using parsimony and Bayesian methods. A family-level phylogeny was estimated to test the monophyly and time of divergence of the South African lineage. This analysis, based on a published ITS phylogeny and an additional ten South African taxa, showed a strongly supported South African clade sister to the campanuloids. Assessment of divergence times using a secondary calibration point suggests that this clade started to diversify during the Oligocene (28 mya), which coincided with global climatic changes from hot wet to cold dry conditions. A phylogenetic analysis of the South African lineage was undertaken based on morphological and DNA sequence data from the chloroplast trnL-F and the nuclear ITS regions. These data sets were analyzed separately and in combination. The phylogenetic hypothesis was used to re-assess the questionable generic boundaries in the family. The ITS data produced poor resolution under parsimony and poor support under Bayesian methods. The resulting phylogenies show five species assemblages that contradict traditional generic circumscriptions, which have primarily been based on the mode of capsule dehiscence. The date estimated for the South African clade was used as calibration point to estimate the age of the clades revealed by the molecular data. Radiation of the Campanulaceae in southern Africa seems to correlate with dramatic climatic and topographical changes such as aridification and continental uplift on the subcontinent that started during the Oligocene. The phylogenetic hypothesis was also used to trace the evolution of nine characters considered important in the circumscription of genera. An uncontradicted synapomorphy was found for the Rhigiophyllum-Siphocodon clade. The fruit character was found to be taxonomically unreliable at the generic level. The phylogeny of the South African clade was further used to focus on the closely related genera, Roella, Merciera and Prismatocarpus â a group forming a well supported clade in most analyses. The total evidence analysis was used to evaluate the status of each of these genera. Several options were explored to translate the phylogeny into a classification. This process was guided by the primary criterion of monophyly followed by stability in nomenclature, strong statistical support for the taxon, maximum phylogenetic information and ease of identification of the taxon. The results favour retaining of Roella, Prismatocarpus and Merciera as separate genera. A synopsis of these three is provided.